STRUCTURAL, ELECTRICAL AND OPTICAL PROPERTIES OF IRON DOPED NiO NANOSTRUCTURE THIN LAYERS - Ghougali, M.; Belahssen, O.; Dogga, A.; Aoun, Y. (University of Eloued جامعة الوادي, 2018)
In this paper we studyed the structural, electrical and optical properties of the pure and iron doped thin layers of nickel oxide prepared at the molar concentration 0.1 mol/L of the nickel nitrate solution (Ni(NO3)2.6H2O) and Iron nitrate solution (FeN3O9.9H2O), thin layers of nickel oxide deposited on glass substrates under the temperature (500oC) by the pyrolytic spray technique. The diffraction results of the X-rays showed that the film layers prepared had a fcc structure and a ominant direction (111). It was noted that there was an increase in light transmission due to doping. Is reached (85%), On the other hand, the results of tests (FTIR) showed the emergence of chemical bonds (Ni-O) and (Fe-O), which appear in the wavenumber range (505-428.2 cm-1), The samples showed a remarkable decrease in electric conductivity after doping. the values of the optical band gap changed between (3.724) and (3.419 eV).
Séminaire National Sur Laser Solaire Et Matériaux ElOeued 5-6 Février 2018
Keywords: STRUCTURAL ELECTRICAL, OPTICAL PROPERTIES, IRON DOPED, NiO NANOSTRUCTURE THIN LAYERS